PENATALAKSANAAN FISIOTERAPI PADA KONDISI OARTA INSUFISIENSI NYHA II - Santi Dwi Kurniasari; Irine Dwitasari Wulandasari; Dinti Mustaqimah (LPPM Universitas Pekalongan, 2011)
Aortic insufficiency is a condition where the valve can not close completely so that when blood flow to part of diastole the left ventricle. Total amount of blood flow was 50 cc of the contents of sekuncup. Thus if the contents sekuncup 70 cc and 30 cc flowing again, the circulation remained normal for the ventricle must pump 100 cc of blood (70 cc to 30 cc circulation is flowing again). So the left ventricle has to work more normally resulting in dilatation and hypertrophy. This resulted in shortness of breath, decreased activity or limited activity, heavy dependence in performing everyday activities, to provide effective and efficient handling, then conducted an examination method of examination shortness of breath with Exertion scale, the noise with auscultation. Things that can help to reduce the problems mentioned above can be done by the method of Breathing Exercise, exercise therapy, early mobilization. The purpose of these modalities is to reduce shortness of breath, prevent the complications of bed rest is pneumonia, improving the ability of heart function and increase the tolerance ability of functional activity and restore the function of physiological, psychosocial, work and get back to optimal can tolerate daily activities.